Cognitive Autonomy and Methodological Individualism: The Interpretative Foundations of Social Life - Di Iorio, Francesco (Springer, 2015)
“Di Iorio offers a new approach to Hayek’s Sensory Order, linking neuroscience to the old Verstehen tradition and to contemporary theories of self-organizing systems; this should be on the reading list of everyone who is interested in Hayek’s thought